Deciphering time-dependent DNA damage complexity, repair, and oxygen tension: a mechanistic model for FLASH-dose-rate radiation therapy - Liew, Hans; Mein, Stewart; Dokić, Ivana; Haberer, Thomas; Debus, Jürgen; Abdollahi, Amir; Mairani, Andrea (International journal of radiation oncology, biology, physics, 2021)
Purpose - Irradiation with ultrahigh dose rates (FLASH) has reemerged as a promising radiation therapy approach to effectively lower potential damage burden on normal tissue without sacrificing tumor control. However, the large number of recent FLASH studies have been conducted under vastly different experimental conditions and circumstances (ie, investigated biological endpoint, radiation quality, and environmental oxygen level), with unverified biological mechanisms of action and unexplored interplay effect of the main dependencies. To facilitate radiobiological investigation of FLASH phenomena and assessment of clinical applicability, we present an extension of the mechanistic radiobiological model “UNified and VERSatile bio response Engine” (UNIVERSE). - Methods and Materials - The dynamic (time-dependent) extension of UNIVERSE was developed incorporating fundamental temporal mechanisms necessary for dose-rate effect prediction, ie, DNA damage repair kinetics [DDRK], oxygen depletion and reoxygenation during irradiation. Model performance in various experimental conditions is validated based on a large panel of in vitro and in vivo data from the literature. The effect of dose, dose rate, oxygen tension, tissue-type, beam quality and DDRK is analyzed. - Results - UNIVERSE adequately reproduces dose-, dose-rate- and oxygen tension-dependent influence on cell killing. For the studied systems, results indicate that the extent of cell/tissue sparing effect, if present at all, strongly depends on DDRK and beam quality used for reference conventional irradiation. A validated mechanistic framework for predicting clinically relevant endpoints comparing conventional and FLASH high-dose-rate effect has been successfully established, relying on time-dependent processing of radiation-induced damage classes taking variable oxygen tension into account. - Conclusions - Highlighted by UNIVERSE itself, the multidimensional nature of this relative sparing effect using high-dose-rate radiation compared with conventional means underlines the importance of robust quantification of biophysical characteristics and consistent, well-documented experimental conditions both in vitro and in vivo before clinical translation. To further elucidate underlying mechanisms and appraise clinical viability, UNIVERSE can provide reliable prediction for biophysical investigations of radiation therapy using ultrahigh dose rate.
Gesehen am 12.08.2021